Transient Gene Expression: an Approach for Recombinant Vaccine Production - Maziar Habibi-Pirkoohi; Amir Ghaffar Shahriari; Mohamad Hamed Ghodoum Parizipour (Pasteur Institute of Iran, 2021)
The production of recombinant vaccines in green plants is an attractive and promising topic in genetic engineering. However, the stable transformation of green plants is a time-consuming, costly, and labor-intensive practice. Moreover, public concerns about genetically modified plants put another limitation on the development and release of transgenic plant-based recombinant vaccines. These shortcomings were addressed by developing transient gene expression systems that allow researchers to investigate candidate recombinant vaccines quickly without tedious work and high costs. A comprehensive literature review was used to gather relevant information. This approach has received much attention in various recombinant vaccine production platforms, including mammalian cell culture, insect cell culture, yeast expression systems, and, more importantly, in plant hosts. Due to their simplicity and efficiency, transient gene expression systems are now widely used to validate gene constructs and transgene expression within plant tissues. This paper describes the concept of transient gene expression and discusses the significant advantages of this approach for producing recombinant vaccines. Notably, the major types of transient gene expression viz. agroinfiltration, viral-based systems, and application of naked plasmid in plant cell culture are introduced, and some examples illustrate the pros and cons of each system. Our literature review also discusses some practical notes on the successful application of this system to provide a more comprehensive image of transient gene expression applicability in green plants. As a whole, this review contributes to the existing literature by shedding more light on various aspects of transient gene expression that have not been addressed thoroughly yet.